Scaling up the benefits of smallholder forestry beyond timber: Success story of teak (Tectona grandis L.f.) leaves marketing in southern Benin. - AOUDJI, KOSSI NOUNAGNON AUGUSTIN; BURNY, Philippe; ADEGBIDI, ANSELME BIENVENU E. ADÉNIYI; GANGLO, COSSI JEAN; Lebailly, Philippe (My University, 2015)
The marketing of teak (Tectona grandis L.f.) leaves was studied in southern Benin, in order to seek out opportunities for increased financial returns in smallholder tree growing. A survey was carried out across the commercialisation system. Seventy six (76) traders were interviewed in nine markets purposely selected, based on their functions in the commercialisation system. Respondents provided information on their marketing functions, the costs borne, and their revenues. The marketing system was led by women who controlled the main functions. Three categories of traders were identified, namely collectors-wholesalers-retailers, collectors-retailers, and retailers. The commercialisation of teak leaves increases the return from tree growing. Traders’ monthly revenue was XOF 4,659–15,927 (USD 9.3–31.9) during the rainy season and XOF 6,621–21,655 (USD 13.2–43.3) during the dry season. As substitute for polyethylene bags in food packaging, teak leaves offer a potential to tackle environmental pollution in southern Benin. The study shows the necessity to consult beneficiaries to ensure the proper selection of tree species in farm forestry programmes.
Keywords: tree growing; livelihood diversification; income; teak leaves; commercialisation; southern Benin.